2018
DOI: 10.3390/foods7070097
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Fish Consumption Desire and Its Factors: A Comparison between the United Kingdom and Singapore

Abstract: It is widely known that rapid population growth and income improvement in some developing countries, and growing health consciousness in some developed countries, are the main factors that have contributed to the global increase in the consumption of fishery products in the past few decades. While a detailed analysis of fish consumption behavior is being conducted in several countries, there are other countries where changes in fish consumption desire and their social and psychological factors are not fully cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 13 publications
2
30
0
3
Order By: Relevance
“…Çolakoğlu et al (2006) also disclosed that there is no association between educational level and fish consumption in Canakkale City of Turkey, while Verbeke and Vackier (2005) found that there is no meaningful relationship between education and fish consumption frequency in Belgium. However, the present findings corroborate the recent revelations by Supartini et al (2018); Can et al 2015and Kaimakoudi et al (2013).…”
Section: Factors Associated With Sea Fish Consumptionsupporting
confidence: 93%
See 1 more Smart Citation
“…Çolakoğlu et al (2006) also disclosed that there is no association between educational level and fish consumption in Canakkale City of Turkey, while Verbeke and Vackier (2005) found that there is no meaningful relationship between education and fish consumption frequency in Belgium. However, the present findings corroborate the recent revelations by Supartini et al (2018); Can et al 2015and Kaimakoudi et al (2013).…”
Section: Factors Associated With Sea Fish Consumptionsupporting
confidence: 93%
“…Perhaps, because educated people are more careful about their health issues than the less educated people. A number of recent studies (Supartini et al, 2018;Can et al, 2015;Kaimakoudi et al, 2013) have indicated association between education and fish consumption. On the other hand, a United States study by Burger et al (1999) shown, however, that there is an opposite association between fish consumption and education where people who did not graduate from high school ate fish more often than those who graduated from high school.…”
Section: Factors Associated With Sea Fish Consumptionmentioning
confidence: 98%
“…Many of these values are consistent with the characteristics of seafood pointed out by Carlucci et al [26] as the promoting factors for consumption. Desire to purchase seafood has increased worldwide and one of the promoting factors of this trend is health benefits [27]. However, there are discussions that consumers also have a perception of potential risks (e.g., contamination caused by micro-organisms, algae bio toxins and chemicals) of seafood consumption, and their perceptions affect seafood purchasing behavior [28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, including Poland, the increasing consumption of meat and meat products is accompanied by an increase in fish and seafood consumption [ 61 , 62 , 63 , 64 , 65 , 66 ]. This trend is determined by economic [ 67 ], psychological [ 61 ], religious [ 62 ], health [ 65 , 66 , 68 , 69 ] factors and product availability [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, including Poland, the increasing consumption of meat and meat products is accompanied by an increase in fish and seafood consumption [ 61 , 62 , 63 , 64 , 65 , 66 ]. This trend is determined by economic [ 67 ], psychological [ 61 ], religious [ 62 ], health [ 65 , 66 , 68 , 69 ] factors and product availability [ 67 ]. However, the increase in fish consumption leading probably to a decreased incidence of cardiovascular disease (due to long-chain n-3-fatty acids and vitamin D contribution) [ 69 , 70 , 71 , 72 , 73 , 74 ] should be considered with the increased concentrations of environmental toxins (polychlorinated biphenyls, poly and perfluoroalkyl substances and methylmercury) [ 73 , 74 ].…”
Section: Introductionmentioning
confidence: 99%